Factors Associated with Women’s Participation in Early Detection of Cervical Cancer at The Pinarik Community Health Center, Padang Lawas Regency 2025 - Ribka Christina Nababan; Felix Kasim; Raisha Octavariny (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Cervical cancer is one of the most common types of cancer affecting women worldwide. This study aims to determine the factors associated with women's participation in cervical cancer early detection at Puskesmas Pinarik, Padang Lawas Regency, in 2025. The results showed that the attitude variable had the most significant influence on women's participation in cervical cancer early detection, with a P value = 0.000 and an Exp(B) value = 186.250. Based on these results, it can be concluded that women's attitudes are the most important factor influencing their participation in cervical cancer early detection. Therefore, Puskesmas Pinarik needs to improve health education and promotion about the importance of cervical cancer early detection for women, so that women can have sufficient knowledge and awareness to undergo early detection and reduce morbidity and mortality rates due to cervical cancer. Thus, it is expected that this study can serve as a reference for Puskesmas Pinarik in increasing women's participation in cervical cancer early detection and reducing the negative impact of cervical cancer on women.